Bioaccumulation of Antimony and Arsenic in Vegetables and Health Risk Assessment in the Superlarge Antimony-Mining Area, China. (9th September 2015) - Zeng, Defang; Zhou, Saijun; Ren, Bozhi; Chen, Tengshu
Abstract : Heavy metal pollution in soils caused by mining and smelting has attracted worldwide attention for its potential health risks to residents. This paper studies the concentrations and accumulations of Sb and As in both soils and vegetables and the human health risks of Sb and As in vegetables from Xikuangshan (XKS) Sb mine, Hunan, China. Results showed that the soils were severely polluted by Sb and As; Sb and As have significant positive correlation. Sb and As concentrations in vegetables were quite different: Coriandrum sativum L. was the highest in Sb, Allium fistulosum L. was the highest in As, and Brassica pekinensis L. was the lowest in both Sb and As; Daucus carota L. and Coriandrum sativum L. showed advantage in accumulating Sb and As; Coriandrum sativum L. had higher capacity of redistributing Sb and As within the plant. Health risk assessment results showed that the hazard quotient (HQ) values of Sb and As in vegetables were in the ranges of 1.61–3.33 and 0.09–0.39, respectively; the chronic daily intake (CDI) and hazard quotient (HQ) values of Sb were over the safe limit recommended by FAO and WHO, indicating that long-term consumption of vegetables from the surrounding soils of XKS mine may bring health risks to residents.